Conceptual learning analysis using CDFs: documents in a computable format: Análisis de aprendizaje conceptual empleando CDFs: documentos con un formato computable - Vílchez Quesada, Enrique (2021)
This article shares the main findings of research carried out in the context of MAT030 Math for Informatics, a course of the Information Systems Engineering, an undergraduate program at the National University of Costa Rica. The main goal of this research was to analyze the impact of the pedagogical integration of the use of a special type of document called CDF (for its acronym in English: computable document format). The research was based on using one-hundred and thirty CDF applications designed by the authors, along with a textbook, as didactic resources to support teaching and self-learning of the contents of MAT030 course. For this, a quantitative methodology was used through two experimental groups with 27 participants and a control group during the first semester of 2020. Five hypothesis tests were executed to analyze the existence of differences in the conceptual understanding of the thematic axes: propositional logic, number theory, set theory, math induction and progressions, and function theory. In addition, a questionnaire was applied to the experimental groups to obtain their most important perceptions about the experience and the quality of the materials designed. The results obtained in the hypothesis tests show an improvement in conceptual understanding and, therefore, in the learning processes within the experimental groups, where the CDF applications played a preponderant role in the development of ways of reasoning, analysis processes, self-evaluation, and visualization of concepts, properties, and algorithms. Also, the experimental groups showed a more favorable academic performance. The research confirms how the appropriate use of educational technology constitutes an instrument that enhances the acquisition of learning skills and logical skills in mathematics education and, therefore, how it can offer a viable alternative to promote an effective combination with a non-traditional approach.